Corrections and an addition to Vermeulen et al. (2014): two new names and a new combination in Bulbophyllum (Orchidaceae; Epidendroideae; Malaxideae) - Vermeulen, Jaap; Schuiteman, André; Vogel, Eduard F. De (Phytotaxa, 2015)
Regrettably, two names in Vermeulen et al. (2014) were not validly published because the basionym references were omitted or incorrectly given (Melbourne Code, 2012: Art. 41.5). In addition, we overlooked Saccoglossum maculatum, which needs a new name in Bulbophyllum. We thank Irina Belyaeva (K) and Anton Sieder (WU) for bringing these omissions to our attention.